Psychosocial outcomes among youth with spinal cord injury by neurological impairment - Riordan, Anne (J Spinal Cord Med, 2015)
OBJECTIVE: Examine psychosocial outcomes of youth with spinal cord injury (SCI) as a function of neurological level (paraplegia/tetraplegia) and severity (American Spinal Injury Association (ASIA) Impairment Scale (AIS)). DESIGN: Survey research. SETTING: Three pediatric SCI specialty centers in the USA. PARTICIPANTS: Youth with SCI ages 5–18 with neurological impairment classifications of: tetraplegia AIS ABC (tetraplegia ABC), paraplegia AIS ABC (paraplegia ABC), or AIS D. OUTCOME MEASURES: Children's Assessment of Participation and Enjoyment, Pediatric Quality of Life Inventory, Revised Children's Manifest Anxiety Scale, and Children's Depression Inventory. RESULTS: Three hundred and forty youth participated; 57% were male; 60% were Caucasian, 21% Hispanic, 7% African-American, 2% Native American, and 3% reported “other”. Their mean age was 8.15 years (standard deviation (SD) = 5.84) at injury and 13.18 years (SD = 3.87) at interview. Ninety-six youth (28%) had tetraplegia ABC injuries, 191 (56%) paraplegia ABC injuries, and 53 (16%) AIS D injuries. Neurological impairment was significantly related to participation and quality of life (QOL). Specifically, youth with paraplegia ABC and AIS D injuries participated in more activities than youth with tetraplegia ABC (P = 0.002; P = 0.018, respectively) and youth with paraplegia ABC participated more often than youth with tetraplegia ABC (P = 0.006). Youth with paraplegia ABC reported higher social QOL than youth with tetraplegia ABC (P = 0.001) and AIS D injuries (P = 0.002). Groups did not differ regarding mental health. CONCLUSION: Interventions should target youth with tetraplegia ABC, as they may need support in terms of participation, and both youth with tetraplegia ABC and AIS D injuries in terms of social integration.